2013
DOI: 10.1007/s11042-013-1568-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low resolution of images on reliability of face detection and recognition

Abstract: In this paper we analyze reliability of the real-time system for face detection and recognition from low-resolution images, e.g., from video monitoring images. First, we briefly describe main features of the standards for biometric face images. Available scientific databases have been checked for compliance with these biometric standards. During the research we have considered both the correctness of extraction (location) of the face from the image as well as the correctness of the identification (based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…have increasing demand to enhance the security in public sectors (Sultana et al, 20104, Kumar and Wu, 2012). Illumination variation and low resolution at operation time are two of the most common causes of quality deviation of non-intrusive biometrics (Marciniak, 2013;Sellahewa and Jassim, 2010). Therefore, in this paper we are proposing a novel non-intrusive multimodal system using face and ear that is capable of adapting uncertain lightning and resolution change.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…have increasing demand to enhance the security in public sectors (Sultana et al, 20104, Kumar and Wu, 2012). Illumination variation and low resolution at operation time are two of the most common causes of quality deviation of non-intrusive biometrics (Marciniak, 2013;Sellahewa and Jassim, 2010). Therefore, in this paper we are proposing a novel non-intrusive multimodal system using face and ear that is capable of adapting uncertain lightning and resolution change.…”
Section: Related Workmentioning
confidence: 99%
“…The value of luminance distortion ranges from 0 to 1. The authors of (Marciniak, 2013) demonstrated that low resolution has serious impact on the performance of biometric recognition. Therefore, we also measured the ratio of resolution degradation of probe image compared to enrolled images.…”
Section: Fuzzy Quality Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the face detection and verification is implemented in many systems and was recently discussed in a number of publications, achieving human-level performance is still a challenge [10]. Robust results are often hard to accomplish in real conditions, because of the influence of such factors as illumination, head position or image quality [6]. Therefore, the evaluation of the algorithms performance in this specific working environment should be made.…”
Section: Introductionmentioning
confidence: 99%
“…Two of them are ISO/IEC 19794-5:2005 [4] and ANSI/INCITS 385-2004 [5]. They describe an example of proper face position in an image [69], where the size of the face is approximately 106 × 96 pixels and the corresponding IPD is about 50 pixels. We use this point to separate high resolution and low resolution.…”
Section: Introductionmentioning
confidence: 99%